IMPLEMENTASI DATA MINING UNTUK MENGETAHUI MANFAAT RPTRA MENGGUNAKAN METODE K-MEANS CLUSTERING - Wardiani, Ditta Sri; Merlina, Nita (Jurnal Pilar Nusa Mandiri, 2019)
The vacant land in DKI Jakarta is increasingly reducing due to the construction of houses, queues, factories, which are increasingly rapid. Making less green open space and water catchment areas. That way, the park of the children to play even decreases, as well as the DKI Jakarta Provincial Government, decides to make a Child-Friendly Integrated Public Room or what we know as RPTRA with facilities that can help the community around it. With this RPTRA, the public especially children can play and interact with each other. Using the K-Means Clustering method can help the government or officers in each RPTRA more easily see how useful this RPTRA and the government also facilitates some of the rooms contained in this RPTRA namely the hall, library, and playroom. The results of this research are the hall that has the highest value for visitors who come where the value obtained is 1319 visitors.